2016
DOI: 10.1039/c6ra18029a
|View full text |Cite
|
Sign up to set email alerts
|

High-performance dielectric ionic ladderphane-derived triblock copolymer with a unique self-assembled nanostructure

Abstract: Ionic poly(bisnorbornene)-based ladderphane can self-assemble into a tree ring-like nanostructure, and exhibits a high dielectric constant, low dielectric loss, narrow hysteresis loop, and good energy density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…We were unable to characterize the actual ratio of cis and trans olefinic protons, due to the broadening of olefinic protons in the resultant poly M2 (Figures S13–S16). The ladderphane structural features of poly M2 is a result of the polymerization step, which also has been observed in other reported structures 25,32 . This is attributed to the presence of di‐oxanorbornene imide moiety functionalized at the bay positions in M2 that can simultaneously undergo ROMP.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…We were unable to characterize the actual ratio of cis and trans olefinic protons, due to the broadening of olefinic protons in the resultant poly M2 (Figures S13–S16). The ladderphane structural features of poly M2 is a result of the polymerization step, which also has been observed in other reported structures 25,32 . This is attributed to the presence of di‐oxanorbornene imide moiety functionalized at the bay positions in M2 that can simultaneously undergo ROMP.…”
Section: Resultssupporting
confidence: 79%
“…This methodology can generate a wide variety of high molecular weight polymers in a controlled regioregular and stereoregular manner 28,29 . To date, only a few examples have been reported for the synthesis of ROMP‐derived PDI‐grafted poly(cycloolefin)s and most of the building blocks have been functionalized at the imide ‐linkage on the PDI pendant 25,30–36 . In 2012, Li et al reported an example of such imide ‐functionalized PDI‐based ladder‐type poly(norbornene)s and studied their supramolecular behavior 31 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerization-induced self-assembly is a convenient method, in which the self-assembly process of block copolymers proceeded in situ in a selective solvent driven by the solubility discrepancy of different blocks. Such a method offers the possibility to prepare the self-assembled nanostructures at industrial scale in an easy and practical way, without the requirement for any post-treatments, such as dialysis or changing the specific mixed solvent composition, which is essential for inducing the conventional self-assembly process of polymers. Since we reported the first example of ROMP-induced self-assembly of block copolymer in one-pot in a selective solvent, there have been research works available in the literature about the metathesis polymerization-induced self-assembly (MPISA) by our group , , and other groups. , In this work, the block copolymer PTNP- b -PSHD could be self-assembled into the core–shell nanostructure with the insoluble PSHD segments as the core and the well-soluble PTNP segments as the shell in the selective solvent of THF (Table S2). Therefore, the postfunctionalization of PTNP- b -PSHD with both different backbones and core–shell nanostructure by TAD modification should be more complex than that of random copolymer with the solely conjugated backbone.…”
Section: Resultsmentioning
confidence: 99%